A long finish - Dibdin, Michael, 1947-2007 (Faber and Faber, 2011)
After his adventures under sun-drenched Neapolitan skies in Cosi Fan Tutti, Aurelio Zen finds himself back in Rome, sneezing in a damp wine cellar and being given another unorthodox assignment: to release the jailed scion of an important wine-growing family who is accused of a brutal murder. Zen travels north to an Italy as outwardly serene as Naples was manic. Amid the quiet fields, autumnal skies and crumbling farmhouses of Piedmont, Zen must try to penetrate a traditional culture in which family and soil are inextricably linked. Here secrets can last for generations, and have a finish as long and lingering as that of a good Barbaresco. Zen must also face up to mysteries from his own past, as well as grapple with the greed, envy, hatred and love that are the human components of any landscape.